One-Year Follow-Up of a Randomized Controlled Trial Piloting a Mindfulness-Based Group Intervention for Adolescent Insulin Resistance - Shomaker, Lauren B.; Pivarunas, Bernadette; Annameier, Shelly K.; Gulley, Lauren; Quaglia, Jordan; Brown, Kirk Warren; Broderick, Patricia; Bell, Christopher (Frontiers in Psychology, 2019)
Introduction: To explore if a brief mindfulness-based intervention (MBI) leads to sustained, improved clinical outcomes in adolescents at-risk for type 2 diabetes (T2D). Methods: Participants were 12-17y girls with overweight/obesity, elevated depression symptoms, and T2D family history participating in a randomized, controlled pilot trial of a six-session MBI versus cognitive-behavioral therapy (CBT) group. At baseline and one-year, mindfulness, depression, insulin resistance (IR), and body composition were assessed with validated instruments. Results: One-year retention was 71% (n=12) in MBI; 81% (n=13) in CBT. At one-year, depression decreased (Cohen’s d=.68) and IR decreased (d=.73) in adolescents randomized to MBI compared to those in CBT. There were no significant between-condition differences in mindfulness, adiposity, or BMI. Discussion: One-year outcomes from this randomized, controlled pilot trial suggest that brief MBI may reduce depression and IR in at-risk adolescents. Replication and exploration of mechanisms within the context of a larger clinical trial are necessary.